Holistic community-based group parenting programs for mothers with maternal mental health issues help address a growing public health need for a diversity of vulnerable mothers, children and families: Findings from an action research study - Aylward, Paul; Sved Williams, Anne (Frontiers in Global Women's Health, 2023)
Background: Maternal mental illness is a major growing global concern which can affect parenting with serious negative implications for offspring. Group-based parenting programs for mothers which both enhance the parent-child relationship and address mental health symptoms in a supportive social setting may optimise better outcomes for mothers and children. The Acorn program in South Australia draws on attachment theory to integrate dance play, reflective diary keeping and therapeutic letters in a holistic program for a diversity of vulnerable mothers and children aged 1-36 months. The program seeks to nurture and enhance parental wellbeing and the quality of the parent-child relationship for mothers experiencing identified mental health illnesses that impinge upon their parenting. This study presents the evaluation of the program and its effectiveness. Methods: Methods: Action research approach for continuous monitoring and program improvement engaging Acorn program staff in evaluation data collection and interpretation of pre and post self-completion measures and standardized observations. Additional data was collected through a telephone interview of attending mothers 6-8 months after program completion to address sustainable impacts on parenting and wellbeing. Results: The program engaged 353 diverse vulnerable mothers with their children. Many had profound overlapping mental health issues including borderline personality disorder (BPD) and depression. The quality of the parent-child interaction, parental confidence, competence and enjoyment were enhanced; mothers’ wellbeing, ability to cope and lasting social supports were augmented. This occurred for a number of ‘most vulnerable’ subgroups including single mothers, mothers with BPD, mothers from non-English speaking households and those with lower levels of education or household income. Mothers reported sustained improvements in their wellbeing, parenting, social and family lives, and feeling closer to their child as a result of participating in the program. Conclusions: Given the high prevalence of maternal mental health issues and substantial potential negative consequences for mothers and offspring, the Acorn parenting program offers an effective means of addressing this pressing public health issue potentially helping large numbers of vulnerable mothers and their children. This has additional gravitas in the shadow of COVID-19 due to expanded numbers of those experiencing greater parental stress, isolation and mental illness.